x (x - 2)*e
d / x\ --\(x - 2)*e / dx
Apply the product rule:
f(x)=x−2f{\left(x \right)} = x - 2f(x)=x−2; to find ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
Differentiate x−2x - 2x−2 term by term:
Apply the power rule: xxx goes to 111
The derivative of the constant (−1)2\left(-1\right) 2(−1)2 is zero.
The result is: 111
g(x)=exg{\left(x \right)} = e^{x}g(x)=ex; to find ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
The derivative of exe^{x}ex is itself.
The result is: (x−2)ex+ex\left(x - 2\right) e^{x} + e^{x}(x−2)ex+ex
Now simplify:
The answer is:
x x e + (x - 2)*e
x x*e
x (1 + x)*e